In vitro selection of Giardia duodenalis for Albendazole resistance identifies a β-tubulin mutation at amino acid E198K. (August 2021) - Emery-Corbin, Samantha J.; Su, Qiao; Tichkule, Swapnil; Baker, Louise; Lacey, Ernest; Jex, Aaron R.
Abstract: Benzimidazole-2-carbamate (BZ) compounds, including Albendazole (Alb), are one of just two drug classes approved to treat the gastrointestinal protist Giardia duodenalis . Benzimidazoles bind to the tubulin dimer interface overlapping the colchicine binding site (CBS) of β-tubulin, thereby inhibiting microtubule polymerisation and disrupting microtubule networks. These BZ compounds are widely used as anthelmintic, anti-fungal and anti-giardial drugs. However, in helminths and fungi, BZ-resistance is widespread and caused by specific point mutations primarily occurring at F167, E198 and F200 in β-tubulin isoform 1. BZ-resistance in Giardia is reported clinically and readily generated in vitro, with significant implications for Giardia control. In Giardia, BZ mode of action (MOA) and resistance mechanisms are presumed but not proven, and no mutations in β-tubulin have been reported in association with Alb resistance (AlbR). Herein, we undertook detailed in vitro drug-susceptibility screens of 13 BZ compounds and 7 Alb structural analogues in isogenic G. duodenalis isolates selected for AlbR and podophyllotoxin, another β-tubulin inhibitor, as well as explored cross-resistance to structurally unrelated, metronidazole (Mtz). AlbR lines exhibited co-resistance to many structural variants in the BZ-pharmacophore, and cross-resistance to podophyllotoxin. AlbR lines were not cross-resistant to Mtz, but MtzR lines had enhanced survival in Alb. Lastly, Alb analogues with longer thioether substituents had decreased potency against our AlbR lines. In silico modelling indicated the Alb-β-tubulin interaction in Giardia partially overlaps the CBS and corresponds to residues associated with BZ-resistance in helminths and fungi (F167, E198, F200). Sequencing of Giardia β-tubulin identified a single nucleotide polymorphism resulting in a mutation from glutamic acid to lysine at amino acid 198 (E198K). To our knowledge, this is the first β-tubulin mutation reported for protistan BZ-resistance. This study provides insight into BZ mode of action and resistance in Giardia, and presents a potential avenue for a genetic test for clinically resistance isolates. Graphical abstract: Image 1 Highlights: In vitro albendazole-resistant Giardia were broadly resistant to benzimidazole-2-carbamates. Cross-resistance to structurally unrelated microtubule inhibitors was observed. The predicted Giardia benzimidazole binding overlaps the colchicine binding site. The E198K β-tubulin mutation was identified in the albendazole-resistant line. Metronidazole-resistance may enhance acquisition of albendazole-resistance.